Secagem de misturas de polpa de frutas tropicais em leito de jorro - Souza, Josilma Silva de (2010)
Drying of fruit pulps in spouted beds of inert particles has been indicated as a viable technique to produce fruit powders. Most of the processes employed to produce dried fruit pulps and juices, such as Foam Mat, encapsulation by co-crystallization and spray drying utilize adjuvant and additives (such as thickeners, coating materials, emulsifiers, acidulants, flavors and dyes), which is not always desirable. The fruit pulp composition exerts an important effect on the fruit powder production using a spouted bed. In the study by Medeiros (2001) it was concluded that lipids, starch and pectin contents play an important role on the process performance, enhancing the powder production; however, the drying of fruit pulps containing high content of reducing sugars (glucose and fructose) is practically unviable. This work has the objective of expanding the studies on drying of fruit pulps in spouted bed with aid of adjuvant (lipids, starch and pectin) aiming to enhance the dryer performance without jeopardizing the sensorial quality of the product. The optimum composition obtained by Medeiros (2001) was the basis for preparing the mixtures of pulps. The mixture formulations included pulps of mango (Mangifera indica), umbu (Spondias tuberosa) and red mombin (Spondia purpurea) with addition of cornstarch, pectin and lipids. Different products were used as lipids source: olive and Brazil nut oils, coconut milk, heavy milk, powder of palm fat and palm olein. First of all, experiments were conducted to define the best formulation of the fruit pulps mixture. This definition was based on the drying performance obtained for each mixture and on the sensorial characteristics of the dry powder. The mixture formulations were submitted to drying at fixed operating conditions of drying and atomizing air flow rate, load of inert particles, temperature and flow rate of the mixture. The best results were obtained with the compositions having powder of palm fat and palm olein in terms of the drying performance and sensorial analysis. Physical and physicochemical characteristics were determined for the dry powders obtained from the mixtures formulations. Solubility and reconstitution time as well as the properties of the product after reconstitution were also evaluated. According to these analyses, the powder from the mixtures formulations presented similar characteristics and compatible quality to those produced in other types of dryers. Considering that the palm olein is produced in Brazil and that it has been used in the food industry substituting the palm fat powder, further studies on drying performance were conducted with the composition that included the palm olein. A complete factorial design of experiments 23, with three repetitions at the central point was conducted to evaluate the effects of the air temperature, feeding flow rate and intermittence time on the responses related to the process performance (powder collection efficiency, material retained in the bed and angle of repose of the inert particles after the process) and to the product quality (mean moisture content, loss of vitamin C and solubility). Powder production was uniform for the majority of the experiments and the higher efficiency with lower retention in the bed (59.2% and 1.8g, respectively) were obtained for the air temperature of 80°C, mixture feed rate of 5ml/min in intervals of 10 min. The statistical analysis of the results showed that the process variables had individual or combined significant influences on the powder collection efficiency, material retention in the bed, powder moisture content and loss of vitamin C. At the experimental ranges of this work, the angle of repose and solubility were not influenced by the operating variables. From the results of the experimental design, statistical models were obtained for the powder moisture content and loss of vitamin C